Journalism, gender and race of senses: the production of identity and difference in the discourse of readers - Stocker, Pâmela (Revista Hipótese, 2016)
The article aims to discuss the emergence of a statement counterhegemonic in the media and the manifestation of the readers about it. The article focuses on the fanpage on Facebook posting of Galileu magazine for the edition of November 2015, on the theme of gender identity. Through discourse analysis, they were examined 233 comments, which led to six "units of meaning": religion, biology, science, ideology, prejudice and role of journalism. We conclude that the speech readers operate in the maintenance of hegemonic cultural maps of meaning.